The effects of internal and external sources of justice on employee turnover intention and organizational citizenship behavior toward clients and workgroup members. Issue 17 (24th September 2020) - Harris, Christopher M.; Lavelle, James J.; McMahan, Gary C.
Abstract: Organizational justice research tends to focus on the effects of fair treatment from organizations or supervisors on employee attitudes and behaviors. Thus, there is a dearth of research on the effects of fair treatment attributable to other parties that employees interact with at work such as coworkers and clients. Controlling for organization-focused and supervisor-focused justice, results from our field study of employees working in a healthcare organization demonstrate that perceptions of client-focused fairness uniquely predicts supervisor ratings of employees organizational citizenship behavior toward clients and that perceptions of workgroup-focused justice uniquely predicts organizational citizenship behavior toward workgroups. Further, we find that client-focused justice perceptions uniquely predict employee turnover intention.